Análise da aplicação de ferrita de cobalto em processo de eletrocoagulação para tratar emulsões oleosas residuais - Vieira, Damaris (2022)
Fossil fuels account for more than 80% of the world's total energy supply. Produced water (AP) corresponds to 98% of all effluents generated in exploration, drilling and production activities. Due to the potential for pollution of the emulsified oil, disposal in water bodies must comply with the required release standards. Among the emerging treatment technologies, this work investigated the application of cobalt ferrites in the electrocoagulation process, in a batch regime, regarding the potential for removal of synthetic emulsified oil. The effect of the factors: distance between electrodes, polarity inversion and ferrite mass were investigated on the removal efficiency. The distance between the electrodes (DE) and the polarity inversion time (TIn) were the significant parameters in the EC process. The presence of the cobalt ferrite factor in the system promoted an increase in the mass gain of the electrode for Tin in 30s. The magnetic separation of the decanted ferrite-oil and supernatant ferrite-sludge set was effective. The percentage of turbidity removal was greater than 96% in all tests. For operating conditions: DE in 1 cm; Tin of 10 s and 0 g of ferrite mass, the TOG removal percentage was 94%.